Tuberculose e o estudo molecular da sua epidemiologia - Pandolfi, J. R. [UNESP]; Malaspina, A. C. [UNESP]; Santos, A. C B [UNESP]; Suffys, P. N.; Oellemann, M. A C; Valentini, Sandro Roberto [UNESP]; Leite, Clarice Queico Fujimura [UNESP] (My University, 2007)
Systems that can distinguish epidemiologically-related Mycobacterium tuberculosis strains from unrelated ones are extremely valuable. Molecular biology techniques have allowed a great deal of information to be acquired about the infectious disease tuberculosis (TB) that was very hard or impossible to obtain by conventional epidemiology. A typing method based on bacterial DNA genome differences, known as RFLP (restriction fragment length polymorphism), is widely used to discriminate strains in the epidemiologic study of TB. However, RFLP is laborious and there is a tendency to replace it by other methods. Thus, other DNA sequences have been employed as epidemiological markers, as in Spoligotyping, a fast technique based on PCR followed by differential hybridization of amplified products. The polymorphism observed among different isolates is probably the product of strain-dependent recombination. MIRU (mycobacterial interspersed repetitive unit) typing is a reproducible and fast assay, involving the generation of genotypes based on the study of 12 loci containing VNTRs (variable-number tandem repeats) in strains of the M. tuberculosis complex. It compares strains from different geographic areas and allows the movement of individual lineages to be tracked, as in RFLP. This approach enables a greater number of isolates to be analyzed, leading to the identification of a larger number of foci of transmission within the population and thus to improved ways of slowing the progress of the disease.

A existência de sistemas que possam diferenciar cepas de Mycobacterium tuberculosis epidemiologicamente relacionadas daquelas não relacionadas, são ferramentas importantes. A tuberculose é uma doença infecciosa, na qual técnicas de biologia molecular permitem a obtenção de informações muito difíceis ou impossíveis de serem alcançadas pela epidemiologia clássica. Um método de tipagem discriminatório, baseado no DNA genômico bacteriano, denominado RFLP (polimorfismo de comprimento de fragmentos de restrição), é empregado no estudo epidemiológico da tuberculose. Entretanto esta técnica é trabalhosa e sua substituição é uma tendência. Assim, outras seqüências têm sido usadas como marcadores epidemiológicos, como na Spoligotyping, a qual é baseada na PCR, com hibridização diferencial subseqüente dos produtos amplificados. O polimorfismo observado nas diferentes amostras é provavelmente produto de recombinação homóloga. A técnica de MIRU (mycobacterial interspersed repetitive unit) é um sistema rápido e reprodutível, onde ocorre a geração de genótipos baseados no estudo de 12 loci contendo VNTRs (número variável de repetições em seqüência) do complexo M. tuberculosis. Ela compara as cepas de áreas geográficas diferentes e permite o rastreamento do movimento de linhagens individuais, como no RFLP. Este tipo de abordagem permite a análise de maior número de cepas e a identificação de um número maior de focos de contaminação dentro da população, propiciando melhores maneiras de frear a transmissão da doença. Palavras-chave: Mycobacterium tuberculosis; tuberculose; epidemiologia molecular; genotipagem.
Tuberculosis and the molecular study of its epidemiology
Keywords: Genotyping; Mycobacterium tuberculosis; Tuberculosis, molecular epidemiology; bacterial DNA; bacterial genome; bacterial strain; bacterium isolate; disease transmission; DNA sequence; epidemic; gene locus; genetic recombination; genotype; human; hybridization; molecular epidemiology; molecular typing; nonhuman; restriction fragment length polymorphism; review; tuberculosis; variable number of tandem repeat